ANALISIS JANGKAUAN PELAYANAN DAN DAYA LAYAN SIRENE PERINGATAN DINI TSUNAMI DI KECAMATAN PADANG UTARA KOTA PADANG - Azahra, Vellyna; Prarikeslan, Widya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
North Padang District is one of the tsunami-prone areas in Padang City, Indonesia, requiring an effective tsunami early warning systemn to reduce disaster risk. This study aimed to analyze the service coverage and serviceability of tsunami sirrens in Norts Padang District. A descriptive quantitative research method with a Geographic Information System (GIS)- based spatial analysis approach was employed. The data included tsunami siren locations, resedential buildings, population data, siren coordinates, and supporting data obtained trough observation, documentation, and relevnt agencies. Spatial analysis was counducted using the buffer, overlay, and spatial join method in ArcGIS 10.8 to evaluate the service coverage and servicebility of tsunami sirens. The result showed that the 300 m service radius covered approximately 134 hektere and residential buildings (16,57%) within the 500 m radius 302 hektere and 6,710 resedential bulldings (43.33%) within the 500 m radius out of 15,487 resedential bildings. These findings indicate that the existing tsunami siren system in North Padang District has not yet provided optimal service coverage and serviceability. Tehrefore, evaluating the current siren llocations and installing additional sirens in uncoverd areas are necessary to improve the effectiveness of the tsunami early warning system.